(untitled) (Eurasian Research Bulletin, 2022)
Relationship terminologies include the terms of address used in different languages or communities for different relatives and the terms of reference used to identify the relationship of these relatives to ego or to each other. As a social symbol kinship terms provide with the information on cultural life of the people who speak the same language. The article describes the role of kin terms in communication. To express unique national features and peculiarities of cultural identity, the article compares kinship terminology in English and Uzbek languages which belong to different language families.